Particulate matters and lung function performances in wood based industries / Nurul Aziemah Che Nazir - Che Nazir, Nurul Aziemah (2014)
Introduction: Wood dust is a complex substance generated from processing of woods in wood based industries. Its composition depends to the species of trees being processed where it is categorized into softwood and hardwood. Objective of this study are to determine the concentration of particulate matter (PM10) and lung function performances, and correlate the exposure to wood dust and lung function performance of workers in wood industries. Methodology: Cross - sectional study was conducted in wood based small medium industries (SMls) located in Selangor. Respondents were (n=32) from production line who were exposed to wood dust. The personal exposure of PM10 was measured using GILLIAN® air sampling pump. Lung function performance of workers was measured using spirometer. Questionnaire was used to obtain the demographic data and respiratory symptoms of workers. Data were analyzed using SPSS version 20. Results: Study found that the mean and standard deviation of PM10 was 2.64 (1.67) mg/m3. The comparison of PM10mean with the standard limit has very strong significance level with p<0.05. As for lung function performances, there were no significant different of lung function between industries. Result shown there was no correlation between exposure to wood dust and lung function of workers. However, there was medium negative correlation between duration of employment and lung function. Conclusion: In conclusion, 12.5% of the workers exposed to wood dust concentration had exceeded the standard limit. Nevertheless, mean of PM10 did not exceed the standard limit. 15.6% of the exposed workers had decreased in their lung function performances. However, there is no significant correlation between wood dust exposure and lung function performances.